2003
DOI: 10.1182/blood-2002-05-1533
|View full text |Cite
|
Sign up to set email alerts
|

Identification of P2Y12-dependent and -independent mechanisms of glycoprotein VI–mediated Rap1 activation in platelets

Abstract: Glycoprotein (GP) VI is a critical platelet collagen receptor, yet the steps involved in GPVI-mediated platelet activation remain incompletely understood. Because activation of Rap1, an abundant small guanosine triphosphatase (GTPase) in platelets, contributes to integrin ␣ IIb ␤ 3 activation, we asked whether and how GPVI signaling activates Rap1 in platelets. Here we show that platelet Rap1 is robustly activated upon addition of convulxin, a GPVI-specific agonist. Using a reconstituted system in RBL-2H3 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
72
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 48 publications
3
72
0
Order By: Relevance
“…One important intracellular pathway which regulates G i -dependent integrin αIIbβ3 activation is constituted by phosphoinositide 3-kinase (PI 3-K) [56, [67][68][69][70]. PI 3-K isoform p110β regulates integrin activation through a classical lipid kinase-dependent mechanism, involving the small GTPase Rap1 and/or the serine-threonine protein kinase B/Akt (PKB/Akt) [71][72][73][74][75][76], whereas p110γ appears to regulate integrin principally through a non-catalytic signalling mechanism [77,78]. Whether other PI3K class I isoforms such as the p110α or PI3K class II or III isoforms, which are highly expressed in blood platelets, play a role in integrin αIIbβ3 activation remains to be determined.…”
Section: Receptormentioning
confidence: 99%
“…One important intracellular pathway which regulates G i -dependent integrin αIIbβ3 activation is constituted by phosphoinositide 3-kinase (PI 3-K) [56, [67][68][69][70]. PI 3-K isoform p110β regulates integrin activation through a classical lipid kinase-dependent mechanism, involving the small GTPase Rap1 and/or the serine-threonine protein kinase B/Akt (PKB/Akt) [71][72][73][74][75][76], whereas p110γ appears to regulate integrin principally through a non-catalytic signalling mechanism [77,78]. Whether other PI3K class I isoforms such as the p110α or PI3K class II or III isoforms, which are highly expressed in blood platelets, play a role in integrin αIIbβ3 activation remains to be determined.…”
Section: Receptormentioning
confidence: 99%
“…Rap 1b is a small GTPase that is activated in a PI3-kinase ␥-dependent mechanism following G␣ i /G␣ z -coupled receptor stimulation. 24,66 It has been shown to play an important role in fibrinogen receptor activation in megakaryocytes. 23 Recent studies have also shown that platelets from Rap 1b knockout mice have a lesser extent of aggregation induced by ADP, compared with the wild-type mouse platelets.…”
mentioning
confidence: 99%
“…In this respect, Larson et al [38] have recently shown that the collagen receptor GPVI-mediated Rap1 activation largely depended on ADP signaling through P2Y 12 , but not through P2Y 1 . In the same context, another study showed that, during thromboxane A 2 mimetic-induced platelet aggregation, signaling through the P2Y 12 receptor by secreted ADP causes positive feedback on platelet secretion through a PI-3 kinase pathway [39].…”
Section: The Platelet P2y 1 and P2y 12 Receptors For Adp Intracellulamentioning
confidence: 99%